IMPLEMENTASI SUPPORT VECTOR MACHINE (SVM) DENGAN QUERY EXPANSION RANKING PADA REVIEW PENGGUNAAN JAMU MADURA - Yunitarini, Rika; Fitrianto, Hambali; Ayu Mufarroha, Fifin (Jurusan Teknik Informatika Fakultas Teknik Universitas Trunojoyo Madura, 2024)
Madura traditional herbal medicine is a traditional herbal medicine made from natural ingredients and is well-known for its efficacy. The popularity of Madura traditional herbal medicine is not only based on the diversity of traditional herbal medicine products and their health benefits, but also on traditional values that have been passed down from generation to generation. One of the most popular Madura traditional herbal medicine is Peluntur traditional herbal medicine. Peluntur traditional herbal medicine is a series of medicinal or herbal products specifically designed as a solution to overcome late menstruation or irregular menstruation, which is often a source of concern for mothers and young women. With the background of the increasing demand for Madura traditional herbal medicine products, a sentiment analysis was conducted on Madura traditional herbal medicine product reviews on the Shopee, Lazada, and Tokopedia applications. This study applies Support Vector Machine and Query Expansion Ranking to achieve the highest accuracy in reviewing the use of Madura traditional herbal medicine. The results obtained for the use of the Support Vector Machine algorithm have an accuracy of 93%, while for the use of the Support Vector Machine and Query Expansion Ranking algorithms at feature selection ratios of 50% and 100% the accuracy increases to 94%.Keywords: Madura traditional herbal medicine, Peluntur traditional herbal medicine, Query Expansion Ranking, Sentiment Analysis, Support Vector Machine